(3eMGSHI GdafGOb hGdeWGYe (B/s - (3ebGHdI, NGdOs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2005)
(3NUGFU GdfTGW GdafObj, eONd Gdi eMGSHI GdafGOb, GdOaGJQ hGdbjhO GdeMGSHjI, eMGSHI GdEjQGOGJ hGdJcGdja, eMGSHI GdehXajf, GdLQO hGdJShjGJ GdLQOjI, GdehGRfGJ GdJNWjWjI, GdJMdjd GdMOj, JMdjd MSGSjI GdQHM, GdJMdjd GdeGdj hGdfSH GdafObjI, eMGSHI GdafGOb HESJNOGe GdceHjhJQ(B.s
(3HHdjhZQGajG(B: (3U(B.309(3; edGMb U(B.325 s
Keywords: (3GdafGObs; (3GdeMGSHIs